THE IMPACT OF LANGUAGE EXPOSURE AND ARTIFICIAL LINGUISTIC ENVIRONMENT ON STUDENTS` VOCABULARY ACQUISITION - Kozhevnikova, Elena (PEOPLE: International Journal of Social Sciences, 2019)
Acquiring wider vocabulary knowledge is an important step for mastering a foreign language and becoming a proficient foreign language speaker. It is commonly assumed that the lack of vocabulary knowledge has a more dramatic effect on clarity and fluency of language than the lack of grammatical knowledge or poor pronunciation.Research conducted by numerous scholars throughout the world has proved that there is an obvious correlation between language exposure and second language acquisition, which also includes vocabulary acquisition. Vocabulary acquisition is an important element of second language acquisition which is hardly possible without language exposure. In case of the lack of natural language exposure artificial linguistic environment is one of the options for language learners. There are multiple ways to improve students` vocabulary and facilitate the process of language acquisition using some methods and tools in and outside the language classroom such as creating artificial linguistic environment in the language classroom and by encouraging language learners to use authentic materials for self-study.